Penerapan Teori Belajar Behavioristik B.F Skinner dalam Memotivasi Siswa pada Pembelajaran PAI di Sekolah Dasar - Lusi Oktavia; Maemonah Maemonah (Instructional Development Journal, 2022)
The background that prompted the researcher to conduct this research was to apply B.F Skinner's learning theory to PAI learning and to be able to motivate students in PAI learning worship materials in class. As we know that there are still many students who experience a decline, especially in their morals. Teachers are responsible for correcting the moral decline that occurs in the classroom, both religious teachers and other teachers. Therefore, Islamic religious education is able to improve, change things that are not good, shortcomings and weaknesses in student beliefs. This relates to the formation of behavior in accordance with the theory of B.F Skinner. The purpose of this study was to find out how the process of applying B.F Skinner's theory in PAI learning in the classroom. With the implementation of learning based on the process of learning theory B.F Skinner is expected to be able to motivate students in the spirit of learning. The method that researchers use in this research is a type of qualitative research. The results showed that with the application of B.F Skinner's theory, students who previously had unruly behavior and lacked learning skills, after applying this theory, students' learning motivation and morals increased.